Enabling electrical response through piezoelectric particle integration in AA2017-T451 aluminium parts using FSP technology - Ferreira, Pedro M. (2024)
Funding Information: PMF acknowledges FCT—Fundação para a Ciência e a Tecnologia for funding the PhD Grant UI/BD/151055/2021. PM F, M A M, C V and M S C acknowledge FCT— Fundação para a Ciência e a Tecnologia for its financial support via Projects UIDB/00667/2020 and UIDP/00667/2020 (UNIDEMI). F W C F acknowledges Fundação para a Ciência e a Tecnologia (FCT-MCTES) for funding the PhD Grant 2022.13870.BD. Publisher Copyright: © 2024 The Author(s). Published by IOP Publishing Ltd.